Virtual Reality-Based Rehabilitation’s Impact on Movement and Quality of Life in Parkinson’s: An Updated Systematic Review of Randomized Controlled Trials - Muvida; Hanif Mustikasari; Yeny Ristaning Belawati; Hana Amatillah (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Parkinson’s disease is a neurodegenerative disorder that can significantly impact an individual’s mobility, balance, and overall quality of life. It is characterized by movement disorders, including tremors, rigidity, bradykinesia, and gait disorder. In addition to pharmacological therapy, rehabilitation approaches play an important role in the management of occurring movement disorders. One of the potential rehabilitation methods is virtual reality (VR). Objective: This systematic review aims to determine the impact of VR-based rehabilitation on balance, mobility, motor function, and the quality of life of Parkinson's patients. Methods: Systematic research was conducted in February 2024 using PubMed, Scopus, and ScienceDirect. A combination of MeSH terms “virtual reality,” “Parkinson,” “exergame,” “effectivity,” and “rehabilitation” was used. The articles selected were randomized controlled trials published in the last ten years in English. The quality of articles was assessed using the Cochrane risk-of-bias tool. Analyses were stratified by outcomes: balance, mobility, motor function, and quality of life. Results: Fourteen randomized controlled trials with 637 patients were included. Most trials show that VR-based rehabilitation significantly improves balance compared to conventional rehabilitation. Mobility and motor function improve in the VR group, but its superiority remains controversial. Improved quality of life is observed, but no trials show statistical significance compared to conventional rehabilitation. Conclusion: This systematic review shows that VR-based rehabilitation has the potential to improve balance, mobility, motor function, and quality of life in Parkinson's patients.